Dashboard To View Petroleum Import Comparison - Sumana, Axcel Lorensius; Tri Sutrisno; Irvan Lewenusa (Jurnal Info Sains : Informatika dan Sains, 2024)
Petroleum is a strategic commodity with an important role in the economy, widely used in the transportation, industrial, and household sectors. In Indonesia, although there are petroleum reserves, domestic production is often insufficient to meet needs. Therefore, importing petroleum products is the main solution. Petroleum product import data covering the volume and value of various types of products is important for strategic decision making in the energy sector. This study aims to design a dashboard that can visualize import data for each petroleum product in real-time, interactively, and easily understood, thus facilitating analysis and supporting better strategic decisions. This dashboard helps users monitor import trends, compare data, and understand national energy needs. As a result, the dashboard is able to display import trends and comparisons interactively based on volume, value, product type, and specific time periods.